Anxiety, depression, and somatic symptom disorders in health care workers at high altitude during the rapid spread of the SARS-CoV-2 Omicron variant: A prospective cohort study - Feng, Xiaokai; Yang, Chenlu; Yang, Huanjuan; Wang, Kai; Xu, Yuanyuan; Zhang, Xiaoxia; Zhang, Qiang; Ma, Juan (Frontiers in Psychiatry, 2023)
Objective The ongoing spread of the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Omicron variant and hypoxia exposure to high altitude are the susceptible factors of people’s psychological abnormalities, especially the health care workers (HCWs) in the front line of the epidemic. There is no dynamic observation data on the prevalence of mental health disorders among HCWs at high altitude. The study is to assess the prevalence of mental health outcomes and its influencing factors among HCWs at high altitude exposed to the SARS-CoV-2 Omicron variant. Methods This prospective cohort study collected sociodemographic data and mental health measurements from 647 HCWs in 3 hospitals in Xining, Qinghai province from 13 April to 4 May 2022. After the mental health intervention for the above-mentioned people in the Chengdong district, we collected mental health indicators on days 7 and 14, respectively. We used the generalized linear model and the generalized estimation equation and for further analysis. Results The baseline cross-sectional survey of 647 HCWs in the Chengdong and Chengbei districts of Xining, Qinghai province shows that the prevalence of depression, anxiety, and somatic disorders were 45.75, 46.52, and 52.55%, respectively. The multivariable model showed that chronic diseases and nucleic acid collection were associated with increased scores of GAD-7, PHQ-9, and PHQ-15. And the GAD-7 score of HCWs with elderly people at home increased by 0.92 points. Subsequent repeated measurements of the mental health of HCWs in Chengdong district in Xining, Qinghai province, showed that anxiety, depression, and somatic disorders were significantly relieved, and physical exercise showed a significant protective effect, while loans and nucleic acid collection showed an adverse effect after 2 weeks of intervention. Additionally, engaged in nucleic acid collection was the risk factor of anxiety and depression. Conclusion In this survey of HCWs on frontline at high altitude during the rapid spread of the SARS-CoV-2 Omicron variant, participants reported experiencing mental health disorders, especially in those with chronic disease, loans, and those who worked with longer hours and engaged in nucleic acid collection in Xining, Qinghai province, China. Exercise may help to improve anxiety and physical disorders.